The Relationship Between Employee Motivation and Work Discipline to the Nurse of the Mongeudong Public Health Center, Banda Sakti District, Lhokseumawe City - Bukhari; Wawan Supandi (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2022)
The IOM (United States Institute of Mediciene), in 2000 made a report